Spo13 protects meiotic cohesin at centromeres in meiosis I - Shonn, Marion A. (Cold Spring Harbor Laboratory Press, 2002)
In the absence of Spo13, budding yeast cells complete a single meiotic division during which sister chromatids often separate. We investigated the function of Spo13 by following chromosomes tagged with green fluorescent protein. The occurrence of a single division in spo13Δ homozygous diploids depends on the spindle checkpoint. Eliminating the checkpoint accelerates meiosis I in spo13Δ cells and allows them to undergo two divisions in which sister chromatids often separate in meiosis I and segregate randomly in meiosis II. Overexpression of Spo13 and the meiosis-specific cohesin Rec8 in mitotic cells prevents separation of sister chromatids despite destruction of Pds1 and activation of Esp1. This phenotype depends on the combined overexpression of both proteins and mimics one aspect of meiosis I chromosome behavior. Overexpressing the mitotic cohesin, Scc1/Mcd1, does not substitute for Rec8, suggesting that the combined actions of Spo13 and Rec8 are important for preventing sister centromere separation in meiosis I.